Iktomi and the berries - Goble, Paul (New York Orchard Books, 1989)
Relates Iktomi's fruitless efforts to pick some buffalo berries.
a Plains Indian story
530L
Keywords: Indians of North American -- Great Plains -- Legends; Folklore